Selective flotation of scheelite from calcite using xanthan gum as depressant. (July 2019) - Dong, Liuyang; Jiao, Fen; Qin, Wenqing; Liu, Wei
Highlights: Flotation separation of scheelite from calcite was difficult. Depressive effect of xanthan gum on calcite was investigated. Xanthan gum can chemically adsorb on calcite surface. Flotation separation of scheelite from calcite can be achieved with xanthan gum. Abstract: Xanthan gum (XG), a clean, non-toxic macromolecular polysaccharide, was studied as a depressant in the flotation separation of scheelite from calcite. Its selective inhibition mechanism was investigated by adsorption experiments, fourier transform infrared spectroscopy (FTIR) analysis and X-ray photoelectron spectroscopy (XPS) analysis. It was found that the XG exhibited a strong selective depressive effect on calcite. However, XG had minimal effect on the flotation recovery of scheelite. Adsorption experiments indicated that the adsorption density of XG on the surface of calcite was much higher than that of scheelite. FTIR results indicated that XG was selectively chemisorbed on calcite surface, while sodium oleate (NaOL) can still be chemisorbed on scheelite surface in the presence of depressant XG. XPS results indicated that the carboxyl groups (COO − ) of the XG can be chemically chelated with the calcium ions species on calcite surface. It was intuitively observed by atomic force microscopy (AFM) that the coverage and adsorption density of XG on calcite surface were higher than that of the scheelite surface. As such, the calcite surface adsorbed more depressant XG than that of scheelite, which hindered the further adsorption of the collector NaOL. This greatly deteriorated the flotation of calcite and achieved flotation separation between the two minerals.